Groundwater resources mapping for small island using Geoelectrical Technique the case study of Ternate Island - M. Pramono Hadi; Ramdani Salam; Rahim Achmad (Faculty of Geography, Universitas Gadjah Mada, 2019)
The measurement of 2D geo-electrical using Wenner Alpha configuration was conducted in the shore line of northern part of Ternate island, in order to know the depth of interface and to analyze the aquifers in conjunction with estimation of ground water potential. Water quality analysis is also conducted in some dug wells, such as in situ water temperature, electrical conductivity, pH, turbidity, dissolved oxygen, and salinity.Due to laboratory analysis, the values of measured parameters of water quality from some dug wells meets to the standards referred, especially for drinking water. The result of interpretation from geo-electrical data showed the depth of interface less than 10m. From a drilled well data near shore line, indicate about 5m deep of interface. Base on geo-electrical survey, water quality analysis and field observation can be concluded that Ternate Island has limited potential of ground water, especially related to amount of fresh ground water. Which is now days, no alternative source yet of clean water for domestic use.